Which Patients Need an Axillary Clearance after Sentinel Node Biopsy?. (24th August 2011) - Pazaiti, Anastasia; Fentiman, Ian S.
Abstract : Sentinel lymph node biopsy (SLNB) is a safe and accurate minimally invasive method for detecting axillary lymph node (ALN) involvement in the clinically negative axilla thereby reducing morbidity in patients who avoid unnecessary axillary lymph node dissection (ALND). Although current guidelines recommend completion ALND when macro- and micrometastatic diseases are identified by SLNB, the benefit of this surgical intervention is under debate. Additionally, the management of the axilla in the presence of isolated tumour cells (ITCs) in SLNB is questioned. Particularly controversial is the prognostic significance of minimal SLNB metastasis in relation to local recurrence and overall survival. Preliminary results of the recently published Z0011 trial suggest similar outcomes after SNB or ALND when the SN is positive, but this finding has to be interpreted with caution.